PEMBERDAYAAN MANARANG (MAMA TERAMPIL CEGAH STUNTING): EDUKASI 1000 HPK UNTUK MENCEGAH STUNTING - Sastriani, Sastriani; Yuliani, Eva; Megawaty, Irna (Jurnal LENTERA, 2026)
development of public health in Indonesia. Many mothers still lack adequate knowledge and skills related to balanced nutrition, appropriate parenting practices, and health behaviors that support optimal child growth and development. This community service activity aimed to examine the effect of nutrition education during the First 1000 Days of Life (HPK) on maternal knowledge regarding stunting prevention in Pamboborang Village, Majene Regency. The MANARANG empowerment program (Skilled Mothers to Prevent Stunting) was implemented through four stages: education on the 1000 HPK, a workshop on preparing complementary feeding (MP-ASI), individual nutrition counseling, and a community awareness campaign. The results showed a significant improvement in maternal knowledge, with the average pre-test score increasing from 6.90 to 7.82 in the post-test, along with a shift in knowledge categories from “poor” and “fair” to “good.” This program proved effective in enhancing mothers’ understanding and skills in